Analisis Faktor- Faktor Yang Mempengaruhi Nilai Tukar Petani Tanaman Pangan Di Indonesia Tahun 2018 – 2022 - Wardana, I Nyoman Krisna; Budhi, Made Kembar Sri (Innovative: Journal Of Social Science Research, 2024)
The research conducted by researchers on this occasion aims to determine the factors that can influence the level of welfare of food crop farmers located in 33 regions of the Indonesian Province by using the Food Farmer Exchange Rate (NTP) indicator from 2018 to 2022. Variables The data used in this research include, among other things, the average net wage in the agricultural sector, rice harvested area, CPI and GRDP in the agricultural sector, as well as the COVID-19 pandemic. Data that provides support for this research includes secondary data that was previously obtained from the Indonesian Central Statistics Agency (BPS), Bulog, Ministry of Agriculture, and also obtained from other sources in the form of other news that directly discusses this research. . The results of this research conducted by the researchers have succeeded in showing that the average net wage in the agricultural sector, rice harvested area, CPI, GRDP in the agricultural sector, and also the COVID-19 pandemic simultaneously influence food NTP in 33 Indonesian Provinces. Partially, the rice harvest area variable and also the COVID-19 pandemic have a positive and significant effect, the CPI and GRDP result variables in the agricultural sector have a negative and significant effect, while the average net wage result variable in the agricultural sector does not have a significant effect on NTP of food crops.